DEVELOPMENT OF STEM-BASED E-MODULE ON SOUND WAVES TO IMPROVE HIGH SCHOOL STUDENTS’ PROBLEM-SOLVING SKILLS - Mutiara Dier; Miftahul Jannah Ritonga; Zulkifli, Zulkifli; Azizahwati, Azizahwati (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study is intended to create a physics e- Module on a sound wave material of Science, Technology and Engineering and Mathematically (STEM) to enhance the problem solving skills of high school students. Researchers are not only generating digital learning products; they are also responsible in offering new innovations; how they can incorporate STEM structures in solving problem skills. The novelty of this study is connected with the use of STEM, which is not oriented on the material only, but a set of scientific thinking operations: defining real-life problems, processing scientific ideas, planning technological outcomes, and mathematically assessing the resulting outcomes. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The resulting product was tested for validity by material, media, and pedagogical experts, and for practicality by teachers and students. Validation results showed that the e-module is highly valid with an average score above 3.26 across all aspects, while the practicality test indicated that the e-module is very easy to use and effective in supporting the learning process. The research results demonstrate that this STEM-based e-module is capable of guiding students to understand the concept of sound waves contextually, training critical and reflective thinking abilities, and systematically improving problem-solving skills. Thus, the main contribution of this research is presenting an e-module development model that utilizes STEM as a methodological framework for problem-based learning on abstract physics material, which has not been widely applied in previous research.